EARLY WARNING SYSTEM (PENGGUNAAN WHATSAPP BOT DI BIDANG KESEHATAN) - Dewi, Riskha Dora Candra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Social media has taken on a new function in recent years, serving as both a source of information and a way to participate and communicate. A same scenario happened with WhatsApp; many people use it to obtain updates on Covid-19’s health. The goal of this project is to use a WhatsApp Bot to investigate the health sector’s early warning system. This study employs a literature review method, which entails examining scholarly publications, books, and research journals. Articles from 2019 to 2021 were selected as inclusion criterion. The findings of the study demonstrate that the usage of WhatsApp Bot in the health industry is critical for early warning systems, particularly during the Covid-19 pandemic. The use of this Whatsapp bot is aimed at assisting healthcare professionals in spotting early warning signs of critically unwell patients in an inpatient hospital, before their clinical state worsens